A Grammar of Mëranaw Language - Aragon, Aimee V (Yayasan Sembilan Pemuda Indonesia, 2023)
This paper describes the grammar of Mëranaw (ISO 639-3: mrw). Mëranaw, or more commonly known as Maranao, is a Philippine language prevalently spoken in almost all parts of Lanao del Sur province and in some areas in Lanao del Norte, Maguindanao, and North Cotabato. The primary goal of this study is to provide a grammar of the Mëranaw language that entails linguistic features of the language covering its morphological features. The participants of this study were the three identified professional and native speakers living in Marawi City. The elicited materials consist of the 615-word list and 775-sentence list from UP Department of Linguistics were transcribed and analyzed using the Basic Linguistic Theory. It was found that morphologically speaking, Mëranaw language has a rich culture of affixation as prefixes, suffixes, infixes, and circumfixes are all present to create new words. These affixations include the prefix p-, mak-, and tomi- and the suffix -an. Moreover, the infix ka- -an and circumfix p- -n, miaka- -e. This is to form another lexical category of a given Mëranaw word that most likely entails to tells the time certain Mëranaw verbs take place. Furthermore, this grammar sketch aims to provide a concrete reference for Mother Tongue–Based Multilingual Education (MTB-MLE) as the Mëranaw language is one of the languages being taught. It further implies language description and documentation as the basis for language revitalization and at the same time culture preservation.